Irritant reactions: a friendly aid in treating warts in children. - Chiriac, A.E.; Azoicai, D. (European Journal of Pediatric Dermatology, 2019)
Warts in children continue to be an annoying and challenging therapeutic issue for physicians and for parents, often a cause of anxiety, especially if the children are small. According to guidelines, there are many therapeutic options, based on different mechanism of action.